"Vieles ist im Fluss. Vieles wird neu werden." - Keller, Sonja E. 1984- (2017)
The article analyzes advertisements of parishes seeking for a new pastor. The author distinguishes types of how the required skills are publically described. This is compared with the actual challenges of the pastoral office.